A mesenchymal chondrosarcoma of the right tibia in a young man requires disarticulation of the right knee: A case study - Youness Mokhchani; Abderrafia Rachdi; Abdelhay Rabbah; Jalal Boukhriss; Bouchaib Chafry; Mustapha Boussouga (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2022)
Chondrosarcoma is a malignant tumor occupying the 2nd position in terms of frequency, all ages combined, after osteosarcoma [1]. Epidemiological data extracted from cancer registries in Europe indicate an annual incidence of ~0.1/100,000 inhabitants [2].